2015
DOI: 10.7773/cm.v41i3.2526
|View full text |Cite
|
Sign up to set email alerts
|

Growth, ammonium excretion, and oxygen consumption of hybrid red tilapia (Oreochromis mossambicus × Oreochromis aureus) grown in seawater and freshwater

Abstract: Growth, ammonium excretion, and oxygen consumption of hybrid red tilapia (Oreochromis mossambicus × Oreochromis aureus) grown in seawater and freshwaterCrecimiento, excreción de amonio y consumo de oxígeno de la tilapia híbrida roja (Oreochromis mossambicus × Oreochromis aureus) cultivada en agua de mar y en agua dulce ABSTRACT. In a comparative study using the hybrid tilapia Oreochromis mossambicus × Oreochromis aureus grown in seawater and freshwater, no significant differences in growth performance (weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Although it has a lower contribution, the WF g for the seed stage poses a potential threat associated with the concentrations of carbon (C) and nitrogen (N) in water, from proteins and carbohydrates contained in the fish feed (25).…”
Section: Analysis Of Cachama Culture Resultsmentioning
confidence: 99%
“…Although it has a lower contribution, the WF g for the seed stage poses a potential threat associated with the concentrations of carbon (C) and nitrogen (N) in water, from proteins and carbohydrates contained in the fish feed (25).…”
Section: Analysis Of Cachama Culture Resultsmentioning
confidence: 99%
“…Additionally, all tilapia are freshwater fish, but their euryhaline capability allows several species and hybrids to adapt and develop in brackish and marine waters (Kamal & Mair 2005; Rahmah et al 2020; Sgnaulin et al 2020). For example, for these fish, the type of metabolic substrate used as the predominant source of energy is not significantly affected, over a wide range of salinity (Barreto‐Curiel et al 2015).…”
Section: Most Important Bft‐based Cultures: Shrimp and Tilapiamentioning
confidence: 99%
“…The salinity content appears to no interfere with the PER values in hybrid red tilapia, as no statistical difference was reported in PER values for juvenile (25 g) reared in fresh (2.08) and seawater (1.97) ( Barreto-Curiel et al, 2015). Freshwater species when exposited to an increasing water salinity use the osmoregulation process to keep the homeostasis of fluids due to the size of the intestine (Verdegem et al, 1997;Chourasia et al, 2018).…”
mentioning
confidence: 99%
“…Research on the hybrid red tilapia (O. mossambicus × O. aureus) is still scarce with few reports on nutritional demands and requirements, and even less under the marine environment (Barreto-Curiel et al, 2015). For example, Botello-Leon et al (2011) reported a successful partial fish meal replacement with sugar cane protein meal (14%) in this hybrid.…”
mentioning
confidence: 99%
See 1 more Smart Citation